Effect of strength training versus raloxifene on bone weight, blood glucose, lipid and antioxidant profile in ovariectomized rats - Santos, Marcos Antônio Pereira dos; Martins, Maria do Carmo de Carvalho e; Silva, Raquel Suelen Brito da; Lopes, Carolina Farias de Arruda; Silva, Alexandre Sérgio (Acta Scientiarum. Biological Sciences, 2023)
We compared the effect of the treatment with strength training (ST) and raloxifene (RALOX) on bone weight, blood glucose, lipid, and antioxidant profile in ovariectomized rats. Twenty-four Wistar rats were distributed into four groups: ovariectomy + VEHICLE (control); ovariectomy + RALOX; ovariectomy + ST; ovariectomy + RALOX + ST. Thirty days after ovariectomy, the animals underwent the treatment with RALOX (750 μcg day-1) and/or ST (three sessions week-1). Thirty days after, all groups were scarified, tibia and femur were weighed, and the blood was collected for analysis of the lipid profile, glucose, and antioxidants catalase (CAT) and glutathione (GSH). The ST group showed greater femur weight (0.82 ± 0.18 g) and RALOX + ST had greater tibia weight (0.61 ± 0.17 g) than CONTROL with femur weight of 0.65 ± 0.08 g and tibia of 0.49 ± 0.08 g with no differences between treatments (p > 0.05). ST group showed significantly higher catalase (181.7 ± 15.4 μM g-1) compared to the other groups. In contrast, the GSH value was lower in ST group (89.2 ± 8.1 μM g-1) compared to RALOX (175.9 ± 17.1 μM g-1) and RALOX + ST (162.8 ± 12.1 μM g-1), but the values of these two groups did not differ from CONTROL (115.3 ± 21.1 μM g-1). Total cholesterol did not differ between groups (p > 0.05), but exercise alone (54.3 ± 2.5 mg dL-1) or with RALOX (53.0 ± 1.5 mg dL-1) resulted in higher HDL cholesterol than CONTROL (45.5 ± 2.5 mg dL-1). Only RALOX+ST presented lower glucose (140.3 ± 9.7 mg dL-1) values than CONTROL (201.7 ± 30.6 mg dL-1). In conclusion, ST promotes similar benefits on bone and metabolic parameters compared to pharmacological treatment in ovariectomized rats.